Geochronological and Geochemical Constraints on the Petrogenesis of Permian Dolerite Dyke Swarms in the Beishan Orogenic Belt, NW China - Xu, Gang; Duan, Jun; Gao, Wenbin; Wang, Rongmin; Shi, Zhen; Ma, Bocheng; Sun, Jia (Frontiers in Earth Science, 2021)
Extensive Early Permian mafic-ultramafic intrusions, doleritic dykes, and basalts crop out within the Beishan area, southern Central Asian Orogenic Belt (CAOB). We present new geochronological and geochemical data for Gubaoquan dolerite dyke swarms in the Beishan orogenic belt. Zircon U-Pb Dating of the Gubaoquan dykes indicates that they were emplaced during the Early Permian (280.7±4 Ma), that was coeval with Yinaoxia and Podong mafic dykes in Beishan area. The dykes are characterized by low Mg# (47-84) in the clinopyroxene crystals, and the content of whole-rock Fe2O3T , MgO and alkali (Na2O+K2O) range from 12.5-17.4wt.%, 4.06-5.51wt.% and 2.8-4.4 wt.%, respectively. The samples from the Gubaoquan dykes have high and variable Ba/La (5.93-14.2) and Ba/Nb (15.0-37.3) ratios but low Th/Yb (0.17-0.24) ratios. The rocks show slightly enrichments in LREE and HFSE, enrichment in Th, Hf and depletion in Nb, Ta. The εNd (t = 280 Ma) values and initial 87Sr/86Sr ratios show variations ranges from 6.4 to 6.8 and 0.706240 to 0.707546, respectively. These data suggest that the parental magmas for the Gubaoquan dykes probably were derived from partial decompressed melting of upwelling depleted asthenosphere mantle that was metasomatized previously by subducted fluids.